2015
DOI: 10.1016/j.jpedp.2015.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐processed food consumption in children from a Basic Health Unit

Abstract: Objectives: To evaluate the contribution of ultra-processed food (UPF) on the dietary consumption of children treated at a Basic Health Unit and the associated factors. Method: Cross-sectional study carried out with a convenience sample of 204 children, aged 2---10 years old, in Southern Brazil. Children's food intake was assessed using a 24-h recall questionnaire. Food items were classified as minimally processed, processed for culinary use, and ultra-processed. A semi-structured questionnaire was applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0
28

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 22 publications
2
18
0
28
Order By: Relevance
“…Few studies have assessed the energy contribution of ultraprocessed foods in children's diets, which is recognized as an important determinant of the nutritional quality of diets (Food and Agriculture Organization, ). Studies carried out with Brazilian children under 10 years old showed that about 40% (variation between 36.1% and 48.6%) of total dietary energy intake came from ultraprocessed foods (Barcelos, Rauber, & Vitolo, ; Bielemann, Santos, dos Santos Costa, Matijasevich, & Santos, ; Leite et al, ; Karnopp et al, ; Sparrenberger, Friedrich, Schiffner, Schuch, & Wagner, ; Rauber et al, ), whereas amongst Colombian children aged 5 to 12 years old, the contribution was 34.4% (Cornwell et al, ). Then, the share of ultraprocessed foods in children's diets in the United Kingdom as observed in this study was almost 1.6 times higher than those observed in the Latin American countries (Barcelos et al, ; Bielemann et al, ; Cornwell et al, ; Karnopp et al, ; Leite et al, ; Rauber et al, ; Sparrenberger et al, ), nations in which dietary patterns are based on unprocessed and minimally processed foods.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have assessed the energy contribution of ultraprocessed foods in children's diets, which is recognized as an important determinant of the nutritional quality of diets (Food and Agriculture Organization, ). Studies carried out with Brazilian children under 10 years old showed that about 40% (variation between 36.1% and 48.6%) of total dietary energy intake came from ultraprocessed foods (Barcelos, Rauber, & Vitolo, ; Bielemann, Santos, dos Santos Costa, Matijasevich, & Santos, ; Leite et al, ; Karnopp et al, ; Sparrenberger, Friedrich, Schiffner, Schuch, & Wagner, ; Rauber et al, ), whereas amongst Colombian children aged 5 to 12 years old, the contribution was 34.4% (Cornwell et al, ). Then, the share of ultraprocessed foods in children's diets in the United Kingdom as observed in this study was almost 1.6 times higher than those observed in the Latin American countries (Barcelos et al, ; Bielemann et al, ; Cornwell et al, ; Karnopp et al, ; Leite et al, ; Rauber et al, ; Sparrenberger et al, ), nations in which dietary patterns are based on unprocessed and minimally processed foods.…”
Section: Discussionmentioning
confidence: 99%
“…Estudos que avaliaram o consumo de alimentos ultraprocessados em crianças com o desenvolvimento típico constataram uma contribuição calórica de alimentos ultraprocessados maior que a do presente estudo. Em uma investigação sobre o consumo alimentar de crianças com idade entre 2 e 10 anos, encontrou-se a contribuição calórica de 47% (6) . Outra pesquisa, realizada com crianças com idade de 7 e 8 anos, mostrou uma contribuição calórica de 48,6% de alimentos processados e ultraprocessados (25) .…”
Section: Discussionunclassified
“…Atualmente, tem sido muito discutida a elevada participação dos alimentos ultraprocessados na dieta infantil. Um estudo transversal (6) realizado em uma Unidade Básica de Saúde no Sul do Brasil, com 204 crianças de 2 a 10 anos, revelou que a contribuição calórica dos ultraprocessados na dieta infantil é elevada. O consumo médio de energia foi de 1.672,3 kcal/dia, sendo 47% dessas calorias provenientes de alimentos ultraprocessados.…”
Section: Introductionunclassified
“…Estudo realizado com 204 crianças de dois a dez anos, no qual agendaram consultas em uma Unidade Básica de Saúde (UBS) de Porto Alegre (RS), teve por objetivo avaliar a contribuição dos alimentos ultraprocessados no consumo alimentar de crianças. Encontrou-se contribuição expressiva de alimentos ultraprocessados na alimentação das crianças estudadas, o que demonstra baixa qualidade no consumo alimentar em relação à presença de alimentos e nutrientes protetores e de risco à saúde, reforçando a necessidade de ações de educação alimentar e nutricional próprias para crianças e pais (SPARRENBERGER et al, 2015).…”
unclassified
“…Diante do exposto, são necessárias ações educativas com pais de alunos de creches em função da influência que as famílias exercem na formação dos hábitos alimentares e na relação do poder aquisitivo com a introdução de alimentos não saudáveis, pois a infância é um importante período para o incentivo e desenvolvimento de práticas alimentares saudáveis (SPARRENBERGER et al, 2015).…”
unclassified